Systematic Development of an Intervention to Promote Self-Sampling for HIV and Sexually Transmitted Infections for Men Who Have Sex With Men: An Intervention Mapping Approach - Leenen, Jeanine; Hoebe, Christian J. P. A.; Bos, Arjan E. R.; Wolffs, Petra F. G.; van Loo, Inge H. M.; de Wit, John B. F.; Jonas, Kai J.; Dukers-Muijrers, Nicole H. T. M. (Frontiers in Reproductive Health, 2021)
Sexual healthcare aims to reduce HIV and sexually transmitted infections (STI) by promoting testing and prevention. To better reach men who have sex with men (MSM), additional strategies are needed. Here we describe development of an intervention, which is part of a broader HIV/STI home-care program, targeted to reach MSM and motivate them to use self-sampling tests. Self-sampling includes blood sampling (finger prick) for HIV, hepatitis B and syphilis, and a urine sample, oral and anorectal swab samples for chlamydia and gonorrhea. Intervention mapping, a systematic six-step approach, was used to guide the development process: 1.Needs assessment including interviews with MSM, 2.Create a matrix of change, 3.Selection of theory-based methods and practical strategies, 4.Intervention development, 5.Implementation plan, and 6.Evaluation (not included in this paper). Stakeholders were involved to increase program support and feasibility. The needs assessment revealed that testing barriers among MSM related to stigma, time, and privacy concerns. Barriers among healthcare providers related to time, competing priorities, lack of expertise, and guideline restrictions. Included intervention components are designed to overcome these barriers, e.g. engaging role models, with a website with a role model story, and providing tailored information. Methods to reach MSM were a variety of information channels (posters, flyers, and audio-visual displays) and delivery modes, such as advertisements on websites, and invitational cards (online and paper) distributed by healthcare providers and MSM themselves (social network-testing/peer-testing). Our intervention aims to encourage MSM to engage in testing, re-testing and providing a test to peer MSM. Evidence-based methods to overcome barriers were included to reach and motivate an increased number of MSM. Using Intervention Mapping stimulated systematic evidence based decision making and adapting the intervention to the target audience and setting. The next step (step 6) is to implement and evaluate the intervention.